EKSISTENSI PESANTREN: ANTARA KULTIVASI TRADISI DAN TRANSFORMASI EDUKASI - Hasan Basri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
This study proves that institution of pesantren (traditional Islamic boarding school) has been transforming in accordance with its characterictics. In early period, pesantren applied traditional system of education; then it grows and develops more dynamic, adaptive, emancipative, and responsive to the development and the progress of age. In fact, pesantren does not let itself fall into a long traditional system but it adapts to and adopts new values both directly and indirectly into educational system. That is why nowadays it is difficult to find pesantren implementing purely traditional system of education. Due to pesantren has been transforming in such a system of education that, typologically, at least, it can be differentiated into three types: firstly, traditional pesantren; secondly, transitional pesantren; and thirdly, modern pesantren. This study conducted by using descriptive-analysis method with social-history approach. Finding out data or information concerning the existence of pesantren, the writer refers to previous studies written by experts and other supported and relevant written matterials.